Microplastic accumulation in benthic invertebrates in Terra Nova Bay (Ross Sea, Antarctica). (April 2020) - Sfriso, Andrea Augusto; Tomio, Yari; Rosso, Beatrice; Gambaro, Andrea; Sfriso, Adriano; Corami, Fabiana; Rastelli, Eugenio; Corinaldesi, Cinzia; Mistri, Michele; Munari, Cristina
Graphical abstract: Highlights: Average microplastic contamination in benthic invertebrates was of 1.0 items individual −1 or 0.7 items mg −1 dw. Microplastic prevalent size ranges were between 50 and 100 μm. The microplastic particles were mainly composed of nylon and polyethylene polymers. The microplastic content was not higher in predators. Bivalves displayed the highest microplastic contamination. Abstract: Microplastic contamination of the benthic invertebrate fauna in Terra Nova Bay (Ross Sea, Antarctica) was determined. Twelve macrobenthic species, characterized by different feeding strategies, were selected at 3 sampling sites at increasing distance from the Italian Scientific Base (Mario Zucchelli, Camp Icarus, Adelie Cove). The 83% of the analyzed macrobenthic species contained microplastics (0.01–3.29 items mg −1 ). The size of the particles, measured by Feret diameter, ranged from 33 to 1000 µm with the highest relative abundance between 50 and 100 µm. Filter-feeders and grazers displayed values of microplastic contamination from 3 to 5 times higher than omnivores and predators, leading to the hypothesis that there is no evident bioaccumulation through the food web. The prevalent polymers identified by micro-FTIR were nylon (86%) and polyethylene (5%); other polymers identified in Antarctic benthos were polytetrafluoroethylene, polyoxymethylene, phenolic resin, polypropylene, polystyrene resin and XT polymer.